Successful Management of a Cesarean Scar Defect with Dehiscence of the Uterine Incision by Using Wound Lavage - Akinori Ida; Yoko Kubota; Maiko Nosaka; Koichi Ito; Hiroshi Kato; Yoshiyuki Tsuji (Case Reports in Obstetrics and Gynecology)
Cesarean scar defects (CSDs) that can be visualized using transvaginal ultrasonography (TVUS) may cause prolonged menstruation, irregular genital bleeding, and secondary infertility; surgical repair is sometimes necessary. We present a case of CSD, with dehiscence of the uterine incision, which was managed using wound lavage. A 38-year-old woman (gravida 4, para 4) had delivered her third and fourth children by cesarean section. Upon the resumption of menstruation, 9 months after her second cesarean section, she demonstrated prolonged menstruation and the presence of a menstrual fistula due to dehiscence of the cesarean section incision from the myometrium to the serosa. We treated the defect by lavaging with a physiological saline solution. After lavaging the wound 3 times, spontaneous healing of the dehiscent muscle layer was successfully achieved. The treatment was complication-free and the healing of the muscle layer has been maintained for more than 8 months.